2023
DOI: 10.1007/s11301-023-00349-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of university-industry collaboration for research, development and innovation: a systematic review

Abstract: Cooperation in research, development and innovation (RD&I) between universities or research institutes and industries plays a fundamental role in the economic development of a country. Industry benefits from state-of-the-art laboratories and technologies from academia, while institutes learn about business reality and market needs. Numerous barriers to the establishment and maintenance of these partnerships have been investigated and reported in the literature, but the information generated by these empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 116 publications
0
13
0
2
Order By: Relevance
“…Furthermore, in another breadth, given that a number of barriers plague collaboration between industry and university, quite a number of studies have devoted considerable efforts to investigating the factors that could drive or inhibit the operations of UIC (e.g. Rossoni et al, 2023;O'Dwyer et al, 2022) and have suggested possible ways by which these obstacles can be attenuated to ensure a successful UIC. These challenges, the literature suggests, if correctly managed, will have a positive effect on the perceived success of UIC, and if neglected, will tend to have a negative impact on making UIC a reality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in another breadth, given that a number of barriers plague collaboration between industry and university, quite a number of studies have devoted considerable efforts to investigating the factors that could drive or inhibit the operations of UIC (e.g. Rossoni et al, 2023;O'Dwyer et al, 2022) and have suggested possible ways by which these obstacles can be attenuated to ensure a successful UIC. These challenges, the literature suggests, if correctly managed, will have a positive effect on the perceived success of UIC, and if neglected, will tend to have a negative impact on making UIC a reality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…University-industry collaboration (UIC) refers to the interaction between different components of the higher education system and industry, with the primary aim of fostering the exchange of knowledge and technology in order to enhance the knowledge base of organisations [29,30]. The upsurge in collaborative activity is a direct result of converging pressures affecting both industry and academia.…”
Section: The University-industry Collaborationmentioning
confidence: 99%
“…In this dynamic partnership, academia serves as a source of creativity, teeming with young, inventive talent, while industry focuses on innovating and advancing new products, processes and services. These innovations not only improve the quality of human life, but also generate significant financial returns [29,35]. Within this framework, participants from universities and research institutes gain a better understanding of the challenges faced by companies.…”
Section: The University-industry Collaborationmentioning
confidence: 99%
See 2 more Smart Citations